"This Is Simply What I Do": Primitive Normativity in Following a Rule - (:unkn) unknown (My University, 2019)
In this paper I propose an account of normativity of meaning that answers the skeptical challenge against meaning which Kripke puts forward on behalf of his reading of Wittgenstein. According to Kripke (1982), the skeptic asks us to identify the fact that constitutes a language user as meaning addition, instead of some other mathematical functions, by “+”. On the view I develop, such facts are facts about a certain type of normative attitude, the primitively normative attitude, that we have as a part of our human nature. In illustrating my account, I start with discussing a similar-sounding proposal that Hannah Ginsborg proposes. The common feature that her account and mine share is the idea that the normativity of meaning is conceptually prior to the notion of meaning. This construal of the normativity of meaning is called “primitive normativity”. In Ginsborg’s proposal, she suggests that the facts which constitute the meaning of words are partly dispositional and partly primitive. I argue that this appeal to dispositions is unsatisfactory. I argue that the facts about our primitively normative attitudes are not subject to dispositional analysis. Rather, we should take those facts as a distinctive kind of their own, which are not subject to any naturalistic analysis.
Keywords: Language; Meaning; Mind; Normativity; Rule-following; Wittgenstein